2010
DOI: 10.1007/s00415-009-5447-1
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction and cardiovascular dysautonomia in Parkinson’s disease

Abstract: Several studies have reported that olfactory dysfunction is an early neuropathological manifestation of Parkinson's disease (PD). Reduced cardiac meta-iodobenzylguanidine ((123)I-MIBG) uptake may be one of the earliest signs of PD. We studied the relation of olfactory dysfunction to cardiovascular dysautonomia in patients with PD. The study group comprised 66 patients with PD (70.5 years) and 26 controls (70.3 years) for olfactory assessment, 21 controls (72.1 years) for cardiac (123)I-MIBG scintigraphy and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 59 publications
2
26
4
Order By: Relevance
“…This conclusion is based on the significantly lower OSIT-J score in patients with PD than the control and its high sensitivity and specificity in the diagnosis. The present results are in agreement with those of previous studies, which showed an OSIT-J score of 4.1-4.8 in patients with PD [3,5,25]. To differentiate PD from the controls, we used cutoff values for OSIT-J of 7, which yielded sensitivity of 81% and specificity of 100% (Table 2).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This conclusion is based on the significantly lower OSIT-J score in patients with PD than the control and its high sensitivity and specificity in the diagnosis. The present results are in agreement with those of previous studies, which showed an OSIT-J score of 4.1-4.8 in patients with PD [3,5,25]. To differentiate PD from the controls, we used cutoff values for OSIT-J of 7, which yielded sensitivity of 81% and specificity of 100% (Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…Another recent study also suggested that olfactory dysfunction in PD is associated with both cardiac sympathetic and parasympathetic dysfunction as well as with vascular sympathetic dysfunction after adjustment for age, disease duration, motor impairment, and dopaminergic medication. As non-motor symptoms, olfactory and autonomic network dysfunctions appear to be closely related in PD [25]. Since most PD patients appear to become anosmic during later stages of the disease, it becomes clear that the correlation between the duration of PD and olfactory function is only relevant in the relatively early stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with PD, olfactory impairment has been correlated with cardiac sympathetic denervation [30, 31], even in the early stages of the disease [32]. Lee et al [33] reported that the degree of cardiac sympathetic dysfunction, as evaluated by cardiac MIBG scintigraphy, was positively correlated with the degree of olfactory identification impairment in patients with PD but not in patients with MSA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in theory, a correlation of olfaction with autonomic function may exist in early PD. Several studies [29] indicated that olfactory dysfunction in PD was significantly related to both cardiac sympathetic and parasympathetic dysfunctions, as well as vascular sympathetic dysfunction. These dysfunctions were respectively reflected by cardiac 123I-MIBG scintigraphy, heart rate variability and orthostatic hypotension.…”
Section: Itemmentioning
confidence: 98%